Acral Melanocytic Neoplasms: A Comprehensive Review of Acral Nevus and Acral Melanoma in Asian Perspective - Sanghyun Park; Sook-Jung Yun (MDPI AG, 2022)
Acral melanocytic neoplasms, including acral melanocytic nevus and acral melanoma, are common melanocytic lesions in Asian populations. Both lesions occur on the volar surface of the hands and feet, and on nail units. Acral melanocytic nevi occur on the arch area of the sole, whereas acral melanomas frequently occur on weight-bearing areas of the sole, and on the fingernails. Therefore, the development of acral melanoma may be associated with chronic pressure, physical stress, or trauma. Dermoscopy is a useful adjunctive diagnostic tool for differential diagnosis. Acral melanocytic nevus is characterized by a parallel furrow pattern, whereas acral melanoma has a parallel ridge pattern. Genetic alterations are also different between the two types of lesion. BRAF and NRAS mutations are common in acral melanocytic nevus, whereas acral melanoma shows lower rates of KIT, NF1, BRAF, and NRAS mutations and remarkable copy number variations in genes such as CCND1, CDK4, hTERT, PAK1, and GAB2. Sentinel lymph node biopsy is important for staging and prognosis. Contemporary treatments for melanoma include targeted therapy for mutations and immunotherapy, such as anti-PD1 inhibitors.